‘Pinky' Tooth: A Rare Faces Of Delayed Tooth Eruption - Wan Abd Razak, Wan Noor Rabiatul Akmalia; Ahmad, Yushaini (IIUM Medical Journal Malaysia, 2017)
Introduction: Delayed tooth eruption (DTE) is the emergence of a tooth into oral cavity that deviates from norms established for different races, ethnics and sexes, which commonly caused either by local or systemic conditions. A case of 10 year-old, Malay girl with unknown underlying medical illness, presented with delayed eruption of maxillary permanent right central incisor. The case history revealed frequent dental abscess around age of 5, followed by dental extraction under local anaesthesia. The clinical examination showed the presence of unerupted tooth 11, elongated but encapsulated with gingiva mimicking a ‘pinky’ tooth. A minimal gingivectomy was carried out to remove the mucosal barrier under topical anaesthesia and tooth 11 erupted completely 2 weeks later without the need for further treatment. This distinct aesthetic problem that affected the child’s self-confidence, can be overcome if was referred earlier. Surgical intervention has produced fast and good outcome for this kind of DTE.